2008
DOI: 10.1088/0953-8984/20/45/455208
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic susceptibility of YbRh2Si2and YbIr2Si2on the basis of a localized 4f electron approach

Abstract: We consider the local properties of the Yb 3+ ion in the crystal electric field in the Kondo lattice compounds YbRh 2 Si 2 and YbIr 2 Si 2 . On this basis we have calculated the magnetic susceptibility taking into account the Kondo interaction in the simplest molecular field approximation. The resulting Curie-Weiss law and Van Vleck susceptibilities could be excellently fitted to experimental results in a wide temperature interval where thermodynamic and transport properties show non-Fermiliquid behaviour for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
26
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 17 publications
5
26
0
Order By: Relevance
“…At first, we use the divergent logarithmic term in g eff ⊥ to reveal the characteristic temperature T GK . Starting values of g-factors were taken from the crystal field consideration (g ⊥ = 3.66) [7], the density of states can be related to the band width of the conduction electrons as ρ = 1/W . The result of the fitting is given in Figure 1a with ρJ = 0.05, θ ⊥ = 0.18 K and T GK = 0.36 K; the latter is by two orders of magnitude smaller than the Kondo temperature T K derived thermodynamically [17] and by transport measurements [18].…”
Section: Comparison With Experiments and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At first, we use the divergent logarithmic term in g eff ⊥ to reveal the characteristic temperature T GK . Starting values of g-factors were taken from the crystal field consideration (g ⊥ = 3.66) [7], the density of states can be related to the band width of the conduction electrons as ρ = 1/W . The result of the fitting is given in Figure 1a with ρJ = 0.05, θ ⊥ = 0.18 K and T GK = 0.36 K; the latter is by two orders of magnitude smaller than the Kondo temperature T K derived thermodynamically [17] and by transport measurements [18].…”
Section: Comparison With Experiments and Discussionmentioning
confidence: 99%
“…In particular, the underlying fluctuations near the QCP can be considered as locally critical, having an atomic length scale [5,6]. On the basis of a localized 4f electron approach we successfully studied the temperature dependence of the static magnetic susceptibility of YbRh 2 Si 2 and YbIr 2 Si 2 at temperatures below T K [7].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of cubic symmetry 0 2 0, B and with isotropic g-factors g( 7 ) = 3g J = 3.429 and g( 6 ) = 7/3g J = 2.667, respectively (see figure 1). Here 6,7,8 are irreducible representations of double cubic group [19].…”
Section: Yb 3+ Ion In Tetragonal Cefmentioning
confidence: 99%
“…We have found that our data are best described by the pure |J z | = 3/2 ground state as shown in Fig.2(b). So far, it has been unclear whether |Γ 1 6 with dominant |J z | = 1/2 or |Γ 1 7 with dominant |J z | = 3/2 forms the ground state [31,32] while a comparison of the slab calculations for subsurface YbRh 2 Si 2 to the low-energy angle-resolved photoemission data has suggested the |Γ 1 7 ground state [33]. Here the |J z | = 3/2 (Γ 7 ) ground state is unambiguously revealed for YbRh 2 Si 2 from our LD in HAXPES at θ = 0 • and 60 • .…”
mentioning
confidence: 99%